Implementation of Problem Based Learning Model through Differentiated Learning in Science and Technology Subjects in Class 5C MI Negeri 5 Sukoharjo - Niken Nur’aini; Meidawati Suswandari (Green Publisher Indonesia, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) Model through differentiated learning in science subjects in class 5C MI Negeri 5 Sukoharjo and identify challenges in its implementation. The research method used is qualitative descriptive with data collection techniques in the form of observation, interviews, and documentation. The results show that the application of PBL combined with differentiated learning helps students in understanding the material of the human respiratory system and makes them more active in the learning process. Differentiated learning is applied based on students' learning styles, namely visual, auditory, and kinesthetic, so that learning strategies and media can be adjusted to individual needs. Teachers use various methods such as videos for visual students, discussion and presentation of material through speakers for auditory students, as well as experiments on making props for kinesthetic students. Despite the challenges of managing more dynamic classrooms and differing levels of student understanding, the strategies implemented support their involvement in learning. In conclusion, the combination of the Problem Based Learning (PBL) Model with differentiated learning is an appropriate strategy in science learning in elementary schools and is in line with the implementation of the Independent Curriculum which is centered on the needs of students.